The Tapestry of detachment and nothingness in Haruki Murakami’s work: an experimental interaction between Nihilism and Zen Buddhism - Saha, Dola (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2024.